Worlding and wilding: Lagos and Detroit as global cities. (April 2016) - Marr, Stephen
A long-standing debate in the urban studies literature emphasises the place of cities in the global cultural, financial and political economy. Traditional approaches to the study of world cities have typically left little room for the cities of the South or the more 'marginal' cities in the West. In this essay, I argue for a more inclusive theoretical and conceptual space that incorporates a broader range of urban situations through a comparative investigation of two cities: Lagos and Detroit. Though they are in some ways peripheral to the functioning of global capitalism, they remain central to its narrative. I therefore suggest that even as Detroit and Lagos undergo experiences of 'wilding' these processes represent an often unacknowledged aspect of 'worlding'. The paper represents a preliminary attempt to centre African and post-industrial cities in the wider critical narrative of contemporary global urbanism.